2022
DOI: 10.1186/s12967-022-03641-y
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 serves as a therapeutic target of adrenocortical carcinoma via regulating epithelial–mesenchymal transition, G2/M phase transition, and PANoptosis

Abstract: Background Adrenocortical carcinoma (ACC) is an extremely rare, aggressive tumor with few effective therapeutic options or drugs. Mitotane (Mtn), which is the only authorized therapeutic drug, came out in 1970 and is still the only first-line treatment for ACC in spite of serious adverse reaction and a high recurrence rate. Methods By in silico analysis of the ACC dataset in the cancer genome atlas (TCGA), we determined that high expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…71 In addition, the activation of pyroptosis, apoptosis and necroptosis (PANoptosis) promotes cancer cell death, thus preventing adrenocortical carcinoma and melanoma development. 72,73 In addition to tumors, PANoptosis also occurs in the process of acute respiratory distress syndrome (ARDS) and acute lung injury, which is manifested by the formation of ASC-caspase-8-RIP3 complex accompanied by caspase-3, GSDMD, phosphorylated MLKL, ZBP1 increased. 74,75 A study showed that genes associated with PANoptosis were differentially expressed in mice middle cerebral artery ischemia-reperfusion injury and control brain tissue samples.…”
Section: Panoptosis In Non-infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 In addition, the activation of pyroptosis, apoptosis and necroptosis (PANoptosis) promotes cancer cell death, thus preventing adrenocortical carcinoma and melanoma development. 72,73 In addition to tumors, PANoptosis also occurs in the process of acute respiratory distress syndrome (ARDS) and acute lung injury, which is manifested by the formation of ASC-caspase-8-RIP3 complex accompanied by caspase-3, GSDMD, phosphorylated MLKL, ZBP1 increased. 74,75 A study showed that genes associated with PANoptosis were differentially expressed in mice middle cerebral artery ischemia-reperfusion injury and control brain tissue samples.…”
Section: Panoptosis In Non-infectious Diseasesmentioning
confidence: 99%
“… 71 In addition, the activation of pyroptosis, apoptosis and necroptosis (PANoptosis) promotes cancer cell death, thus preventing adrenocortical carcinoma and melanoma development. 72 , 73 …”
Section: Panoptosis and Diseasesmentioning
confidence: 99%
“…6D). Cell cycle kinase family member Cyclin-dependent kinase 1 (CDK1) signi cantly impacts cell cycle progression [16,17] . CDK1 overexpression has been found in many cancers, including gastric cancer, ovarian cancer, oral squamous cell carcinoma, liver cancer, and breast cancer [18] .…”
Section: Analysis Of Esco2-related Regulatory Pathwaysmentioning
confidence: 99%
“…Cyclin-dependent kinase 1 (CDK1) belongs to a family of cell cycle kinases that are involved in the transition of the cell cycle from the G2 to M phase of mitosis, and upon abnormal regulation, uncontrolled cell proliferation would occur, which would eventually cause tumorigenesis [33]. In ACC, high expression of CDK1 accelerates the epithelial-mesenchymal transition (EMT) while promoting cell proliferation, in addition to altering the cell cycle by regulating the interactions of UBE2C and AURKA/B [34]. An in vitro experiment exploring the interaction between CDK1 and centromeric protein (CENPF) revealed that the G2/M phase transition and cell proliferation were activated during mitosis in the ACC cell line SW13 under the effects of CDK1 and CENPF, which could essentially explain the poor prognosis of ACC [35].…”
Section: Categorymentioning
confidence: 99%